2015
DOI: 10.1007/s00384-015-2295-6
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat accumulation affects risk of colonic diverticular hemorrhage

Abstract: This study presents new information on risk factors for diverticular bleeding. A large volume of visceral adipose tissue, but not BMI or SAT, appears to entail a risk for diverticular bleeding, after age, gender, metabolic factors, and antithrombotic drugs use adjustments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…In a casecontrol study in Japan, risk factors for DH included the use of ATDs and NSAIDs, hypertension, diabetes, arteriosclerotic diseases such as ischemic disease mellitus and chronic kidney disease, age ≥ 70 years, obesity [13,15,17,18] . Our study also found higher rates of use for both ATDs and NSAIDs, higher age and male sex, obesity, smoking, alcohol drinking, and arteriosclerotic diseases in patients with colonic DH compared to those with bleeding from other causes.…”
Section: Discussionmentioning
confidence: 99%
“…In a casecontrol study in Japan, risk factors for DH included the use of ATDs and NSAIDs, hypertension, diabetes, arteriosclerotic diseases such as ischemic disease mellitus and chronic kidney disease, age ≥ 70 years, obesity [13,15,17,18] . Our study also found higher rates of use for both ATDs and NSAIDs, higher age and male sex, obesity, smoking, alcohol drinking, and arteriosclerotic diseases in patients with colonic DH compared to those with bleeding from other causes.…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggested that the assertive therapeutic approach including endoscopic hemostasis might decrease the costs of hospitalization of patients with colonic diverticular bleeding [27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an association has been demonstrated between an increased incidence and severity of complicated diverticular disease [54]. In particular data coming from a population study have shown that among several factors such as hypertension, dyslipidemia, and chronic kidney disease, increasing BMI and increasing visceral adipose tissue were associated with diverticular bleeding [55].…”
Section: Diverticulosismentioning
confidence: 99%